Uniaxial Tensile Load of Lattice Structures Produced by Metal Additive Manufacturing - Hanzl, Pavel; Zetkova, Ivana; Dana, Milan (Manufacturing Technology Journal, 2019)
Lightweight constructions are in demand for applications which require low weight accompanied by rigidity. From this perspective, lattice structures are an interesting design solution in conjunction with additive manufacturing technology. This study addresses promising lattice topologies. A range of metallic lattice structures was produced using Direct Metal Laser Sintering technology and the samples were exposed to uniaxial tensile load. During the tensile tests crack initiations and locations of the breaks were observed. The results clarify the weaknesses of the cellular lattices and reveal their maximum tensile load. First steps have been taken to meet the demand for optimized lightweight AM products.
Keywords: Lattice Structures; Rigid Constructions; Additive Manufacturing; Selective Laser Melting; Direct Metal Laser Sintering